2009
DOI: 10.1099/vir.0.010553-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of smallpox vaccines using variola neutralization

Abstract: The search for a ‘third’-generation smallpox vaccine has resulted in the development and characterization of several vaccine candidates. A significant barrier to acceptance is the absence of challenge models showing induction of correlates of protective immunity against variola virus. In this light, virus neutralization provides one of few experimental methods to show specific ‘in vitro’ activity of vaccines against variola virus. Here, we provide characterization of the ability of a modified vaccinia virus An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
30
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 21 publications
(19 reference statements)
1
30
0
2
Order By: Relevance
“…As has been reported in other clinical studies evaluating MVA [1013, 1518] or first- and second-generation live smallpox vaccines [14], the total antibody response is higher, both in terms of the number of responders and in the magnitude of the response, compared with neutralizing antibody titers. Although neutralizing antibodies are considered an important immunological correlate of protection [22], other antibody functions such as complement fixation, antibody directed cellular cytotoxicity, and opsonization have been shown to play an important role in protection as well [2327].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…As has been reported in other clinical studies evaluating MVA [1013, 1518] or first- and second-generation live smallpox vaccines [14], the total antibody response is higher, both in terms of the number of responders and in the magnitude of the response, compared with neutralizing antibody titers. Although neutralizing antibodies are considered an important immunological correlate of protection [22], other antibody functions such as complement fixation, antibody directed cellular cytotoxicity, and opsonization have been shown to play an important role in protection as well [2327].…”
Section: Discussionsupporting
confidence: 70%
“…Recent trials with MVA as a stand-alone smallpox vaccine have demonstrated a favorable safety profile [1013]. Modified vaccinia Ankara was also shown to induce immune responses comparable with conventional VACV-based vaccines [14, 15]. Populations at an increased risk to receive first- and second-generation smallpox vaccines (ie, subjects with HIV-infection [16], atopic dermatitis [17], or immune-suppressive therapy [18], respectively) tolerated vaccination with MVA well and had a good immune response.…”
mentioning
confidence: 99%
“…However, a two-dose regimen of IMVAMUNE ® has been shown to provide a similar antibody response as Dryvax ® [9], reduced the size of replicating vaccinia takes [9,28] and was as effective if not better than Dryvax ® in producing peak 90% variola virus neutralization GMTs [39,40]. The two-dose SC MVA regimen remains the standard against which other regimens/doses are compared until more data are available.…”
Section: Discussionmentioning
confidence: 95%
“…If the ability to neutralize variola is the desired outcome of smallpox vaccination, then understanding the relative significances of variola and vaccinia neutralization titers is a critical surrogate measure, especially if previous measures of vaccine efficacy (i.e., the Jennerian pustule or "take") are not available for third-generation vaccines and if variola stocks are destroyed. The comparable efficacy of a vaccination regimen using vaccinia (Dryvax or modified vaccinia Ankara [MVA]) or variola virus as the neutralizing target is presented elsewhere (3,4). Sera (from 46 participants) from a National Institutes of Health-funded smallpox vaccine trial (DMID 02-017) were evaluated at Saint Louis University (SLU) and at the Centers for Disease Control and Prevention (CDC).…”
mentioning
confidence: 99%
“…Immunostained plaques were counted using a dissecting microscope. Variola PRNT assays were performed at the CDC using a method adapted from that previously described (3,4). Duplicate 2-fold dilutions of sera were prepared in RPMI 1640 supplemented with 2% fetal bovine serum, mixed with variola virus strain Solaimen (final serum dilutions of 1:10 to 1:40 for prebleeds and 1:40 to 1:1,280 for postvaccination sera), and incubated at 35°C overnight.…”
mentioning
confidence: 99%